Fostering Distance Education: Lessons From a United States-England Partnered Collaborative Online International Learning Approach - Ingram, Lucy A.; Monroe, Courtney; Wright, Hayley; Burrell, Amy; Jenks, Rebecca; Cheung, Simon; Friedman, Daniela B. (Frontiers in Education, 2021)
Collaborative Online International Learning (COIL) is a teaching and learning approach whereby entire courses or modules are co-developed and team taught by instructors from different institutions for students of both institutions. Since 2006, the approach has been gaining in mass appeal; however, considering our present-day global coronavirus pandemic, COILs have a renewed relevance in academia. Faculty from the University of South Carolina (U.S.) and Coventry University (England) embarked on a COIL partnership yielding a valuable experience that can serve as a model for other institutions that are interested in developing innovative and cross-cultural distance learning opportunities. We explain how the institutional partnership emerged, describe the course content, and provide lessons that our team learned through the COIL development and implementation process. Our experience as a first-time COIL partnership is a model for others to consider as the landscape for the academic enterprise expands the confines of brick-and-mortar institutions.